The association betweeen conative functioning of adolescents exposed to intimate partner violence and family dimensions of cohesion and adaptibility - simonović grujic, Ljiljana branislav (Vojnosanitetski pregled, 2021)
Abstract Bаckground/Aim. Childhood exposure to various types of emotional, physical and sexual abuse in intimate partner violence (IPV) families is associated with difficulties in emotional and social adjustment, including conduct problems, internalized and externalized symptoms. The aim of this study was to determine the relationship between intimate partner violence and: family system functioning (cohesion and adaptability), conative functioning of adolescents and risk of psychopathological symptomatology development. The specific aim of this study was to establish the mental hygiene and preventive measures in order to reduce the negative consequences of growing up in the IPV families. Methods. The study was done on a sample of 308 adolescents, aged 15–18 years, divided into the IPV group (n = 68 adolescents growing up in families with the IPV and exposed to IPV in which the violence was reported and processed), and the control group (n = 240 adolescents coming from families in which there was not found any type of violence or psychosocial pathology on the basis of the results obtained on the Conners' Parent Rating Scale–Revised (CPRS-R) Questionnaire. The Faces III scale of measurement was used for measuring the dimensions of family functioning, and Cybernetic model of conative dimensions of personality (CON-6) for conative functioning of adolescents. The data was processed by using the discriminate and linear regressive analysis. Results. The adolescents growing up in the families with the IPV and exposed to IPV showed the statistically significant differences (p < 0.01) in conative functioning: psychosomatic β = -.509, anxiety β = -.393, aggressive β = -.398, dissociative β = -.509 and adaptive personality reactions β = -.455, as compared to the control group. There was 32.35% of adolescents exposed to IPV who showed the pronounced pathological values regarding social-adaption reaction, 23.53% regarding pathological anxiety and 23.53% dissociative reactions. The greatest negative relationship was found between intimate partner violence and family dimension of cohesion (β = -0.605, p < 0.01). Conclusion. Adolescents growing up and being exposed to the intimate partner violence were significantly associated with changes in the conative functioning and risk of externalized and internalized symptoms development in socially-adaptive, anxiety and dissociative reactions and the need to introduce the preventive mental-hygienic measures. The mediator between IPV and conative functioning of adolescents was family cohesion
Keywords: behavior; mental disorders; adolescent; family; violence; adaptation, psychological; impulsive behavior